First Animal Source Metagenome Assembly of Lawsonella clevelandensis from Canine External Otitis - Adrienn Gréta Tóth; Norbert Solymosi; Miklós Tenk; Zsófia Káldy; Tibor Németh (Pathogens)
External otitis is one of the most common conditions in dogs to be presented to the veterinarian. Moreover, the disorder is often challenging to manage. The range and role of microorganisms involved in the pathogenesis are currently not fully understood. Therefore, the condition has been studied using third-generation sequencing (Oxford Nanopore Technology) to gain a more complete picture of the pathogens involved. Throughout the metagenome assembly of a sample from the ear canal of an 11-year-old female Yorkshire terrier suffering from chronic external otitis, a genome of Lawsonella clevelandensis was compiled. To our knowledge, this result is the first of its type of animal origin. The outcome of the assembly is a single circular chromosome with a length of 1,909,339 bp and 1727 predicted genes. One open reading frame associated with antimicrobial resistance could have been identified. Comparing all available genomes, the species can be associated with three main genome clusters. The finding contributes to the extending knowledge bank about this often-overlooked pathogen and raises attention to the role of nanopore sequencing by the identification and characterization of microorganisms that are difficult to culture.